Investigating boredom among EFL teachers - Dumančić Dino (ExELL (Explorations in English Language and Linguistics))
The aim of this qualitative study was to investigate boredom among Croatian primary and secondary school teachers of English. The data was gathered by means of an open-ended survey that focused on the teachers’ experiences with classroom boredom. The findings pointed to different causes of boredom in the Croatian FLT context, such as grammar tasks and uninteresting subject matter. Croatian teachers reported various manifestations of boredom, i.e. cognitive and motivational, as well as diverse emotion regulation strategies employed, such as introducing new content or engaging in physical activity. Majority of the teachers stated that boredom did not affect their instructional quality, however there were those who reported having observed adverse effects in their classrooms.